2014
DOI: 10.3389/fnins.2014.00019
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental factors in severe psychiatric disorders

Abstract: During the last decades, schizophrenia has been regarded as a developmental disorder. The neurodevelopmental hypothesis proposes schizophrenia to be related to genetic and environmental factors leading to abnormal brain development during the pre- or postnatal period. First disease symptoms appear in early adulthood during the synaptic pruning and myelination process. Meta-analyses of structural MRI studies revealing hippocampal volume deficits in first-episode patients and in the longitudinal disease course c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
168
0
20

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 269 publications
(188 citation statements)
references
References 170 publications
(187 reference statements)
0
168
0
20
Order By: Relevance
“…A number of genes have been associated with the risk to develop schizophrenia (4)(5)(6). In addition to genetic predisposition, environmental factors, such as urbanicity (7), obstetric complications (8), or exposure to early life stress (ELS) (9,10), are known to increase the risk of developing schizophrenia. Such genome-environment interactions are mediated by epigenetic processes, including DNA methylation (DNAme) or histone modifications (11).…”
Section: Hdac1 Links Early Life Stress To Schizophrenialike Phenotypesmentioning
confidence: 99%
“…A number of genes have been associated with the risk to develop schizophrenia (4)(5)(6). In addition to genetic predisposition, environmental factors, such as urbanicity (7), obstetric complications (8), or exposure to early life stress (ELS) (9,10), are known to increase the risk of developing schizophrenia. Such genome-environment interactions are mediated by epigenetic processes, including DNA methylation (DNAme) or histone modifications (11).…”
Section: Hdac1 Links Early Life Stress To Schizophrenialike Phenotypesmentioning
confidence: 99%
“…Data about the role of obstetric complications in major depressive disorder are even more scanty than in bipolar disorder (Schmitt et al, 2014). Three independent studies found that preterm birth was associated with a higher risk of a depressive disorder in adolescence (Patton et al, 2004) or adulthood (Räikkönen et al, 2007;Nosarti et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Muchas de estas alteraciones han sido codificadas desde el nacimiento por genes defectuosos, aunque son desenmascaradas en el tiempo por procesos complejos como la poda neuronal. Es de notar que este último fenómeno, que es fisiológico y se da entre la pubertad y la adolescencia, coincide frecuentemente con la edad de inicio de las primeras alteraciones psicopatológicas presentes en las psicosis (44,45) …”
Section: O De Murray Y Lewis (42)unclassified